2018
DOI: 10.1088/1361-6528/aad129
|View full text |Cite
|
Sign up to set email alerts
|

Electron trapping at SiO2/4H-SiC interface probed by transient capacitance measurements and atomic resolution chemical analysis

Abstract: Studying the electrical and structural properties of the interface of the gate oxide (SiO) with silicon carbide (4H-SiC) is a fundamental topic, with important implications for understanding and optimising the performances of metal-oxide-semiconductor field effect transistor (MOSFETs). In this paper, near interface oxide traps (NIOTs) in lateral 4H-SiC MOSFETs were investigated combining transient gate capacitance measurements (C-t) and state of the art scanning transmission electron microscopy in electron ene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In particular, SCM in cross sections showed that the faceted 4H-SiC surface morphology incorporates a larger nitrogen amount compared to the basal planes, because it exposes different ratios between (0001) and (11−20) planes [47]. Other studies based on transmission electron microscopy (TEM) [52,53] and X-ray photoemission spectroscopy (XPS) [49] demonstrated that nitrogen is incorporated within a couple of 4H-SiC crystalline monolayers.…”
Section: Effects Of Counter Doping and Interface Stressmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, SCM in cross sections showed that the faceted 4H-SiC surface morphology incorporates a larger nitrogen amount compared to the basal planes, because it exposes different ratios between (0001) and (11−20) planes [47]. Other studies based on transmission electron microscopy (TEM) [52,53] and X-ray photoemission spectroscopy (XPS) [49] demonstrated that nitrogen is incorporated within a couple of 4H-SiC crystalline monolayers.…”
Section: Effects Of Counter Doping and Interface Stressmentioning
confidence: 99%
“…Many studies reported on the V th instability upon negative gate bias stress on MOSFETs [9, 52,70]. However, to get insights on the basic trapping mechanisms of NIOTs in the insulator, it is useful to analyse the behaviour of p-type MOS capacitors ( Figure 11) [71].…”
Section: Charge Trapping Phenomenamentioning
confidence: 99%
See 3 more Smart Citations